International monetary policy spillovers through the bank funding channel - Peter Lindner; Axel Loeffler; Esther Segalla; Guzel Valitova; Ursula Vogel (Oesterreichische Nationalbank (OeNB), 2018)
In this paper, we examine the international transmission of monetary policies of major advanced economies (US, UK, euro area) through banks in Austria and Germany. In particular, we compare the role of banks' funding structure, broken down by country of origin as well as by currency denomination, in the international transmission of monetary policy changes to bank lending. We find weak evidence for inward spillovers. The more a bank is funded in US dollars, the more its domestic real sector lending is affected by monetary policy changes in the US. This effect is more pronounced in Germany than in Austria. We do not find evidence for outward spillovers of euro area monetary policy through a bank funding channel.
Keywords: E52; F33; G21; 330; monetary policy spillover; global banks; bank funding channel